THE ROLE OF THE FAMILY ENVIRONMENT IN THE FORMATION OF DEVIANT BEHAVIOR AT A YOUNG AGE - Aliqulova Nargiza (Journals Park Publishing, 2022)
Deviant behavior is a human activity or behavior, a social phenomenon that does not comply with the norms of morality established in society, and many other similar cases of deception, laziness, theft, drunkenness, drug addiction, suicide and many others are the characteristics of this behavior. And the adolescent period is a favorable period for the formation and development of deviant behavior.
Keywords: deviant behavior; adolescence; alcohol abuse